The politics of inheritance in Romans - Forman, Mark, 1972- (Cambridge ; New York : Cambridge University Press, 2011)
"Mark Forman explores the extent to which Paul's concept of 'inheritance' in Romans, and its associated imagery, logic and arguments, served to evoke socio-political expectations that were different to those which prevailed in contemporary Roman imperial discourse. Forman explores how Paul deploys the idea of inheritance in Romans and analyses the sources which inform and overlap with this concept. Coins, literature and architecture are all examined in order to understand the purpose, hopes and expectations of first-century society. This book contributes to recent studies covering Paul and politics by arguing that Paul's concept of inheritance subverts and challenges first-century Roman ideologies"--
Includes bibliographical references (p. 244-264) and index.
Description based on print version record.
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc; Inheritance and succession -- Biblical teaching; RELIGION / Biblical Studies / New Testament; RELIGION / Biblical Studies / Paul's Letters; Electronic books